2005
DOI: 10.1590/s1415-47572005000400014
|View full text |Cite
|
Sign up to set email alerts
|

Satellyptus: analysis and database of microsatellites from ESTs of Eucalyptus

Abstract: The main goal of our research was to search for SSRs in the Eucalyptus EST FORESTs database (using a software for mining SSR-motifs). With this objective, we created a database for cataloging Eucalyptus EST-derived SSRs, and developed a bioinformatics tool, named Satellyptus, for finding and analyzing microsatellites in the Eucalyptus EST database. The search for microsatellites in the FORESTs database containing 71,115 Eucalyptus EST sequences (52.09 Mb) revealed 20,530 SSRs in 15,621 ESTs. The SSR abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
(34 reference statements)
4
26
0
Order By: Relevance
“…Our study clearly illustrates that ESTs are a useful source of new SSR markers for citrus that are polymorphic and can be transferred between species and related genus. A number of reports have demonstrated that EST databases are a very good source of polymorphic markers for many organisms, including plants (Delseny et al, 1997;Scott et al, 2000;Kantety et al, 2002;Ceresini et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study clearly illustrates that ESTs are a useful source of new SSR markers for citrus that are polymorphic and can be transferred between species and related genus. A number of reports have demonstrated that EST databases are a very good source of polymorphic markers for many organisms, including plants (Delseny et al, 1997;Scott et al, 2000;Kantety et al, 2002;Ceresini et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the relative position of a SSR within a given sequence we used the strategy adapted by Ceresini et al (2005) that categorized the microsatellites as initial (I, close to the 5' end), middle (M) or end (E, close to the 3' end). Mononucleotides were excluded from this analysis.…”
Section: Microsatellite Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…SSRs were analyzed for type, abundance, and distribution (genic and intergenic regions). A total of 1,567 SSRs were identified, with an average frequency of 1.26 SSR per kb, which is a low EV Tambarussi et al frequency compared to the rice chloroplasts (6.5 SSR per kb) (Rajendrakumar et al 2007) and is higher when compared with Eucalyptus ESTs (0.37 SSR per kb) (Ceresini et al 2005) and Citrus ESTs (0.5 SSR per kb) (Palmieri et al 2007). This was expected since the occurrence of particular microsatellite motifs and repeats (especially the non-trimeric ones) could have implications on how the gene coding region is transcribed, due to risks of frameshift mutations (Metzgar et al 2000).…”
Section: Frequency and Distribution Of Ssrs In Genic And Intergenic Rmentioning
confidence: 94%
“…From a total of 1,785,569 bp that represents these plastomes, we identified 2427 cpSSRs, with an average frequency of 1.36 cpSSR per kb, which is higher than that of Eucalyptus ESTs (expressed sequence tags) (0.37 SSR per kb) (Ceresini et al, 2005) and Citrus ESTs (0.5 SSR per kb) (Palmieri et al, 2007). This was expected since the occurrence of particular microsatellite motifs and repeats (especially the non-trimeric ones) could have implications on how the gene coding region is transcribed due to risks of frameshift mutations (Metzgar et al, 2000).…”
Section: Frequency and Distribution Of Cpssrs In The Poaceae Species mentioning
confidence: 97%